Musculoskeletal Pain in Elderly in a City in Southern Brazil: Prevalence and associated factors (Research, Society and Development, 2021)
Musculoskeletal pain in the elderly affects functional capacity and influences increased frailty, comorbidities and mortality. The aim of the study was to evaluate the prevalence of musculoskeletal pain and associated factors in the elderly population. This is a cross-sectional study, using data from the Elderly Cohort Project in Bagé-RS: health situation and relationship with the Family Health Strategy (FHS), carried out during the 2016/2017 follow-up. The sample consisted of 735 elderly people, aged 68 or over, residing in the area covered by primary health care services in the urban area of the municipality of Bagé / RS. The Nordic Musculoskeletal Questionnaire (NMQ) was used to analyze prevalence of pain in the upper limbs, spine and lower limbs and to verify associated factors. Information on the symptoms in these regions of the body was used. The majority elderly of whom were female (65.4%) aged between 68 and 79 years (68.7%) and white skin color (82.2%). Prevalence of musculoskeletal pain in the spine was 42.5%, 33.7% in the upper limbs and 31.0% in the lower limbs. In the crude and adjusted analysis association of pain was maintained with the presence of multimorbidity, greater satisfaction with health and use of emergency services in the last year. The results of this study reinforcing the pattern of pain and musculoskeletal symptoms in the elderly and justifying the need for training professionals and health services to serve this growing portion of the population.